The Effect of Phytobiotic Bidara Leaf Powder (Ziziphus mauritiana) in Feed to the Percentage of Carcass and Abdominal Fat of Hybrid Duck Un-Sexed (Un-Equal) - Irfan H. Djunaidi; Azizah, Siti; Ampodee, Kremlin Mark (Journal of Agriprecision & Social Impact, 2025)
The research investigated the effect of adding phytobiotics in basal feed on live weight, carcass weight, carcass percentage, and abdominal fat percentage of hybrid ducks. The hybrid ducks used for research were 192 ducks. The method used in this research was field experimental with a Completely Randomized Design (CRD) using four treatments and six replications there were basal feed + 0% phytobiotics (T0), basal feed + 0.20% phytobiotics (T1), basal feed + 0.25% phytobiotics (T2) and basal feed + 0.30% phytobiotics (T3). The variables measured were the percentage of carcasses and abdominal fat. The research data were analyzed using variance using the Completely Randomized Design and continued with Duncan's multiple range test to determine whether there were fundamental or real differences. The result showed that the addition of phytobiotics in basal feed to the live weight, carcass weight, carcass percentage, and abdominal fat percentage of hybrid ducks adding leaf flour in hybrid duck feed had no significant effect ( P> 0.05) on body weight before slaughtering, carcass percentage of thigh and wing parts and abdominal fat. But as a significant impact (P <0.05) on carcass weight and a very substantial effect (P <0.01) on the percentage of carcass breast.